A compilation of quantitative functional traits for marine and freshwater crustacean zooplankton. Issue 4 (8th April 2016) - Hébert, Marie‐Pier; Beisner, Beatrix E.; Maranger, Roxane
Abstract: This data compilation synthesizes 8609 individual observations and ranges of 13 traits from 201 freshwater and 191 marine crustacean taxa belonging to either Copepoda or Cladocera, two important zooplankton groups across all major aquatic habitats. Most data were gathered from the literature, with the balance being provided by zooplankton ecologists. With the aim of more fully assessing zooplankton effects on elemental processes such as nitrogen (N), phosphorus (P) and carbon (C) stocks and fluxes in aquatic ecosystems, this data set provides information on the following traits: body size (length and mass), trophic group, elemental and biochemical corporal composition (N, P, C, lipid and protein content), respiration rates, N‐ and P‐excretion rates, as well as stoichiometric ratios. Although relationships for zooplankton metabolism as a function of body mass or requirements have been explored in the past three decades, data have not been systematically compiled nor examined from an integrative and large‐scale perspective across crustacean taxa and habitat types. While this contribution likely represents the most comprehensive assembly of traits for both marine and freshwater species, this data set is not exhaustive either. As a result, this compilation also identifies knowledge gaps: a fact that should encourage researchers to disclose information they may have to help complete such databases. This trait matrix is made available for the first time in this data paper; prior to its release, the data set has been analyzed in a meta‐analysis published as a companion paper. This data set should prove extremely valuable for aquatic ecologists for trait‐based characterization of plankton community structure as well as biogeochemical modeling. These data are also well‐suited for deriving shortcut relationships that predict more difficult to measure trait values, most of which can be directly related to ecosystem properties (i.e., effect traits), from simpler traits (e.g., body size), and for exploring patterns of trait variation within and amongst taxonomic units or ecosystem types. Overall, this data set is likely to provide new insights into the functional structure of zooplankton communities and increase our mechanistic understanding of the influence of these pivotal organisms on aquatic ecosystems.